Current Concepts in Medical Research and Practice (Neuroscience and Respiration ;, 2018)
Change is an inherent feature of all aspects of clinical practice and patient management. This book seeks to contribute to presenting novel knowledge in various fields of clinical work. The articles tackle transdisciplinary topics and focus on the underlying mechanisms of clinical disorders, their prevention and management. The themes addressed include allergy and pseudoallergy in the pediatric population, influenza-related infections and their sequelae, which continues to be a scourge in the developing world, the risk of lung cancer repeats and their management, viral hepatitis that may lead to hepatocarcinoma, respiratory consequences of diaphragmatic hernias, disorders of steroid hormone metabolism, and others. The articles bring the updated strategies, research, and best practices to improve outcomes and to deliver state-of-the-art clinical care to patients. The book will be of interest to physicians, academic scientists, and researchers who are keen in sharing the latest medical practice developments.